2022
DOI: 10.1049/elp2.12284
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of consequent pole permanent magnet synchronous motor with low torque ripple

Abstract: Permanent magnet (PM) motor with consequent pole (CP) rotor can improve the PM utilisation ratio. However, one group of PMs with the same polarity is replaced by iron core, which deteriorates the electromagnetic performances of the motor, including asymmetric air-gap magnetic field and larger torque ripple. To solve this problem, this study analyses the relationship between the torque ripple and the stator-rotor magnetomotive force (MMF) harmonics, determines the harmonic orders causing the torque ripple of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As a local optimization methodology, the Taguchi method can optimize multiple motor performance parameters at the same time, with fewer tests, lower costs and a shorter design cycle. By using the designed orthogonal test, design time and cost can be saved, and the optimal parameter combination can be found at the fastest speed [24]. Moreover, it can reduce the influence of various noise factors.…”
Section: Taguchi Methods Optimizationmentioning
confidence: 99%
“…As a local optimization methodology, the Taguchi method can optimize multiple motor performance parameters at the same time, with fewer tests, lower costs and a shorter design cycle. By using the designed orthogonal test, design time and cost can be saved, and the optimal parameter combination can be found at the fastest speed [24]. Moreover, it can reduce the influence of various noise factors.…”
Section: Taguchi Methods Optimizationmentioning
confidence: 99%
“…This is due to the uneven air gap between the stator and rotor. Therefore, the waveform of the air-gap magnetic field is sinusoidal, and the effective harmonic content of the air-gap magnetic density is improved [20][21][22]. Compared with IPMSMA, the average output torque of IPMSMB is increased by 4.36 Nm, while the torque ripple is reduced to 6.19%.…”
Section: Analysis Of Load Torquementioning
confidence: 99%
“…By comparing the motor performance under different shapes of permanent magnet poles, Song et al showed that the biased letter poles can effectively weaken the tooth slot torque [6]. In addition, there are slotted stator teeth [7], pole offset [8], eccentric distance [9], permanent magnet segmentation [10], and other slotted torque weakening methods.…”
Section: Introductionmentioning
confidence: 99%